Bojungikki-Tang Improves Response to PD-L1 Immunotherapy by Regulating the Tumor Microenvironment in MC38 Tumor-Bearing Mice - Chun, Jaemoo; Park, Sang-Min; Yi, Jin-Mu; Ha, In Jin; Kang, Han Na; Jeong, Mi-Kyung (Frontiers in Pharmacology, 2022)
Immune checkpoint blockage targeting PD-L1 has led to breakthroughs in cancer treatment. Although anti-PD-L1-based immunotherapy has been approved as standard therapy in various cancer types, its therapeutic efficacy in most colorectal cancers (CRC) is still limited due to the low response to immunotherapy. Therefore, combining treatment with herbal medicines could be an alternative approach for treating CRC to overcome this limitation. Bojungikki-tang (BJIKT), a herbal formula used in traditional Chinese medicine, clinically improves the quality of life for cancer patients and has been associated with antitumor and immune-modulating activities. However, the regulatory effect of BJIKT on the immune response in the tumor microenvironment remains largely uninvestigated. In this study, we verified the inhibitory effect of BJIKT on tumor growth and investigated the regulatory effect of combination therapy with BJIKT and anti-PD-L1 on antitumor immune responses in an MC38 CRC-bearing C57BL/6 mouse model. Immune profiling analysis by flow cytometry was used to characterize the exact cell types contributing to anticancer activities. Combination treatment with BJIKT and anti-PD-L1 therapy significantly suppressed tumor growth in MC38-bearing mice and increased the proportion of cytotoxic T lymphocytes and natural killer cells in tumor tissues. Furthermore, BJIKT suppressed the population of myeloid-derived suppressor cells, suggesting that this combination treatment effectively regulates the immunological function of T cells by improving the tumor microenvironment. The herbal formula BJIKT can be a novel therapeutic option for improving anti-PD-L1-based immunotherapy in patients with CRC.